Comparison of triglyceride-glucose related indices in prediction of cardiometabolic disease incidence among US midlife women - Duo Yang; Xiang Li; Chao Qu; Jiayi Yi; Hai Gao (Scientific Reports)
Abstract The effects of triglyceride-glucose (TyG) related indices on cardiometabolic disease (CMD) are still unclear. Our study aimed to investigate the relationship between the TyG-related indices and CMD risk among midlife women. This retrospective observational cohort study utilized data from the 2020 SWAN participants. The TyG index was computed as Ln [fasting triglyceride (mg/dL) × fasting glucose (mg/dL)/2]. Modified TyG indices were created by integrating TyG with body mass index (BMI), waist circumference (WC), and waist-to-height ratio (WHtR). Multivariate Cox proportional hazards regression and receiver operating characteristic (ROC) analyses were conducted to assess the associations and predictive capacities of TyG and its related indices with CMD incidences. The mean age of participants was 45.7 years, comprising 420 (20.8%) Black, 184 (9.1%) Chinese, 225 (11.1%) Japanese, and 1191 (58.9%) Caucasian or Hispanic women. Over a 10-year follow-up, 837 women (41.4%) developed CMD. Compared to the lowest quartile, the adjusted hazard ratios (95% confidence intervals) for incident CMD in the highest quartile for TyG, TyG-BMI, TyG-WC, and TyG-WHtR were 1.78 (1.41–2.25), 3.26 (2.51–4.24), 3.13 (2.41–4.06), and 3.19 (2.47–4.12), respectively. The area under the ROC curve for modified TyG indices was significantly higher than that for the TyG index alone. Both the TyG and modified TyG indices were significantly associated with new-onset CMD, with modified TyG indices showing superior performance in identifying individuals at risk for CMD.